The sustainability of local economic development projects in Thulamela Municipality in the Vhembe District of the Limpopo Province - Nghonyama, Matimba George (University of Limpopo (Turfloop Campus), 2011)
Local Economic Development has been a focal point for the African National Congressled government since the mid-nineties. It has been one of the ways to redress the injustices of the apartheid regime and to make it possible for the historically disadvantaged individuals to be incorporated into the formal economy and to engage in poverty alleviation programmes which focus on them. The government has already spent millions of rands in funding Local Economic Development projects whose primary goal is poverty alleviation. The purpose of this study was to determine the sustainability of Local Economy Development projects in Thulamela Municipality with the main aim being to determine those factors that enhance the sustainability of a project vis-a-vis those factors that hinder the sustainability of a project. The study took place in Thulamela Municipality of Vhembe District in Limpopo Province, South Africa. A qualitative study was conducted with thirteen (14) participants that included 6 LED projects managers (Brick-Laying Project A has 2 Managers), 6 Community Development Practitioners, a local LED Manager and an LED Officer from the Department of Agriculture. Data was collected with the use of semi-structured interviews and questionnaires. The findings of the study largely confirm what other researchers have already discovered, such as: the role played by the educational level of the beneficiaries of these projects on the success of their projects. The managers of the two best performing projects have post-matric qualifications while the managers of the least performing projects have only grade 12. The two top performing projects also keep proper accounting records and both use the services of an independent auditor to conduct their audits, while the least performing projects (Brick-Laying Project A, Poultry Project C and Poultry Project B) use ad-hoc accounting records and do not carry out financial audits. The majority of the members of these projects, as in most rural areas, are women. However, interestingly, the best performing projects have male managers. One noteworthy finding is that all but one project (Cooperative Project E) had a large number of members leaving the project since their establishment, with Cooperative Project D and Brick-laying Project A being the worst affected. The researcher sees this as an indication that most beneficiaries do not have the patience to persevere. They see LED projects as ‘get-rich quick’ schemes where they expect to earn a lot of money. When they realize that they will not be earning as much as they had hoped for most beneficiaries become de-motivated and leave. The researcher therefore suggests that further in-depth research be conducted on the factors that lead to LED projects losing members as opposed to employing more people. A research study could also be conducted to determine the role of keeping proper accounting records in the sustainability of LED projects. Furthermore, the fact that the least performing projects were those that are headed by women, further research needs to be conducted to determine whether gender plays a role in the success of projects.
Thesis (M.Dev.)) --University of Limpopo, 2011
Keywords: Economic development; 338.968; Economic development; Developing countries -- Economic policy